A new approach to the control of autolevelling for drafting process: part 2: experimental verification. Issue 2 (1st February 2019) - Ma, Baolong; Wang, Jun
Abstract: The unevenness plays a dominant role in discussing the autolevelling results of drafting process. Part 2 of the paper presents the experimental verification of the discrete autolevelling model, which was elaborated on the basis of a discrete-event simulation that was set up in Part 1 of the paper. A new device was designed and constructed with progressive drive and control mechanisms to realize the autolevelling approach during drafting process. The experimental results have showed that the discrete autolevelling model contributes to lower the unevenness of drafting process and improve the quality of output strands. The principle of autolevelling of this model is also analyzed in a further step.